A PRELIMINARY STUDY ON ACADEMICS' JOB PERFORMANCE DISPARITIES IN WORKING FROM HOME (WFH) PRACTISES - Azwan Shah Aminuddin; Intan Nurul’ain Mohd Firdaus Kozako; Nooradzlina Mohd Pauzi; Nooradzlina Mohd Pauzi; Atiela Amran (Journal of Islamic, Social, Economics and Development, 2023)
WFH has been used in the workplace since the 1970s and is known for promoting a healthier work-life balance and can offer many benefits to both the organization and its employee, also known as teleworking or telework, these practices are widely implemented around the world during pandemic COVID-19 since March 2020. As in Malaysia, the relevance of today’s work arrangement that is now being questioned due to the current pandemic situation had driven the researcher to examine the relationship between the impacts of telecommuting work arrangement and employee performance during the Movement Control Order (MCO) due to COVID-19 pandemic. The telecommuting work arrangement has played a significant role in Malaysia nowadays and it has become one of the mechanisms to ensure business continuity. This study will further collect a response from academic staff in UiTM by using a set of questionnaires distributed online. By addressing the issues, it is strongly believed that the findings from this study will contribute to the significant development of WFH policies and guidelines for company practices ensuring employees are performing their job meeting the expectation even though not in a conventional office setting.